2022
DOI: 10.1038/s41375-022-01697-9
|View full text |Cite
|
Sign up to set email alerts
|

A primary hierarchically organized patient-derived model enables in depth interrogation of stemness driven by the coding and non-coding genome

Abstract: Many cancers are organized as cellular hierarchies sustained by cancer stem cells (CSC), whose eradication is crucial for achieving long-term remission. Difficulties to isolate and undertake in vitro and in vivo experimental studies of rare CSC under conditions that preserve their original properties currently constitute a bottleneck for identifying molecular mechanisms involving coding and non-coding genomic regions that govern stemness. We focussed on acute myeloid leukemia (AML) as a paradigm of the CSC mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…To characterize in depth the pool of LSC in OCI-AML22, we performed single cell (sc) multiome analysis (scATAC-Seq/scRNA-Seq) on 7,160 cells isolated from the LSC-enriched CD34+CD38-fraction ( in vivo LSC frequency is 1 in 200) 34 (Figure 1A). The majority of these cells were enriched for stem cell programs when mapped onto a single cell transcriptomic map of stem and progenitor populations from healthy human bone marrow (Supplementary Figure 1A) 41 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To characterize in depth the pool of LSC in OCI-AML22, we performed single cell (sc) multiome analysis (scATAC-Seq/scRNA-Seq) on 7,160 cells isolated from the LSC-enriched CD34+CD38-fraction ( in vivo LSC frequency is 1 in 200) 34 (Figure 1A). The majority of these cells were enriched for stem cell programs when mapped onto a single cell transcriptomic map of stem and progenitor populations from healthy human bone marrow (Supplementary Figure 1A) 41 .…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that core stemness properties of LSC that drive clinical outcomes and treatment sensitivity are shared across AML patients, and support studies to understand whether the basis for the observed functional heterogeneity within the LSC compartment may also be shared. The gold standard for studies of functional properties of LSC has been AML patient-derived xenograft (PDX) assays, as most AML cell lines do not exhibit a LSC-driven hierarchy that captures patient biology 34 . However, PDX assays are laborious, difficult to standardize and cannot be tailored for high-throughput studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AML LSCs mainly reside within populations of CD34 + CD38 − AML cells and can reconstitute human AML in immunodeficient mice. Although recent studies have suggested that LSCs also exist in other AML fractions, 34 immature CD34 + CD38 − cells remain the best characterised and most potent population initiating leukaemia in various xenograft mouse models and re‐transplantation experiments 5,35–37 . Here, we assessed the therapeutic effects of abemaciclib in two clinically relevant AML PDX models established by xenotransplantation of primary LSC populations from relapsed patients (PDX‐1 and PDX‐2) into NCG mice (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Although recent studies have suggested that LSCs also exist in other AML fractions, 34 immature CD34 + CD38 − cells remain the best characterised and most potent population initiating leukaemia in various xenograft mouse models and re-transplantation experiments. 5,[35][36][37] Here, we assessed the therapeutic effects of abemaciclib in two clinically relevant AML PDX models established by xenotransplantation of primary LSC populations from relapsed patients (PDX-1 and PDX-2) into NCG mice (Figure 2A). In this model, abemaciclib treatment suppressed the growth of primary human AML cells (Figure 2B) and led to a lower average size and weight of the spleen in abemaciclib-treated xenografted mice (Figure 2C).…”
Section: Abemaciclib Induces Differentiation and Loss Of Leukaemic St...mentioning
confidence: 99%